MMAP-05 PHASE I STUDY OF CONCURRENT PAXALISIB AND RADIATION THERAPY IN PATIENTS WITH SOLID TUMOR BRAIN METASTASES OR LEPTOMENINGEAL METASTASES HARBORING PI3K PATHWAY MUTATIONS: RESULTS FROM THE DOSE-ESCALATION COHORT. (5th August 2022) - Yang, Jonathan; Mann, Justin; Pike, Luke; Zinovoy, Melissa; Young, Robert; Offin, Michael; Mitchell, Ryan; Kazarian, Arousiak; Shadat, Tamim; Garner, James; Simpson, Jeremy; Friend, John; et al.
Abstract: INTRODUCTION: Radiation therapy (RT) is an effective treatment for patients with central nervous system metastases, but disease control is poor in patients with tumors that harbor PI3K pathway alterations. We hypothesized that combining RT with paxalisib, a CNS-penetrant small molecule PI3K/mTOR inhibitor, could abrogate this effect via downregulation of prosurvival pathways. METHODS: This is a single institution, open-label, phase I trial of concurrent paxalisib and RT (NCT04192981) for patients with brain metastases, leptomeningeal metastases, or both with PI3K pathway mutations. Part A comprised a standard 3 + 3 dose escalation of paxalisib at 45mg, 60mg, or 75mg daily for two weeks with concomitant RT. The primary objective was to establish the maximum tolerated dose (MTD) of paxalisib when combined with cranial RT. RESULTS: Between 3/2020-1/2022, 12 patients were enrolled to Part A, of which 9 were evaluable (3 did not complete protocol therapy). Median followup was 4.5 months (0.9-14.9 months). All patients received paxalisib with whole brain RT (30Gy in 10 fractions)- 10 patients for brain metastases, and 2 for leptomeningeal metastases. The most common histology was breast cancer (4 [33%]), and the most common PI3K pathway alterations were PIK3CA mutation (7 [58%]). No patient experienced dose-limiting toxicity (DLT) at 45mg paxalisib daily with concurrent RT, and 2 experienced DLT at 60mg paxalisib: 1 with grade 3 nausea and vomiting and 1 with grade 4 enterocolitis and neutropenia. When combined with cranial RT, the paxalisib MTD was established at 45mg/day. We also observed robust response with all evaluable patients experiencing partial or complete response per RANO-BM within 3 months of protocol therapy. CONCLUSION: A MTD of 45mg/day has been established for paxalisib with concurrent cranial RT in patients with solid tumor brain metastases and leptomeningeal metastases harboring PI3K pathway mutations. Additional patients are being recruited to an expansion cohort at this dose (Part B) to confirm safety and preliminary evidence of activity.